Marital status as an independent prognostic factor for patients of malignant pleural mesothelioma - Pan, Shu; Yan, Na; Zhao, Yuanyuan; Li, Zhiwen (Frontiers in Medicine, 2022)
Objectives The prognostic impact of marital status on malignant pleural mesothelioma (MPM) is not investigated. This paper probes into the relationship between the prognosis of MPM and marital status. Materials and methods The Surveillance, Epidemiology, and End Results (SEER) database of American had been applied to choose eligible patients over the 2004–2015 periods. Moreover, cancer-specific survival (CSS) and overall survival (OS) of unmarried and married groups were compared. Results A total of 3,997 patients in total had been identified, including 2,735 (68.43%) married patients. In comparison to unmarried patients, married ones tended to be younger, male, white, and received active treatment (surgery, chemotherapy, or radiotherapy). In addition, the 1, 3, and 5-year CSS rates were 44.40, 12.09, and 6.88% in married patients, while 35.75, 12.12, and 6.37% in unmarried group (p = 0.0014). At the same time, the 1, 3, and 5-year OS rates were 41.84, 10.56, and 5.91% in married patients, while 33.67, 10.44, and 4.93%, respectively, in the unmarried group (p < 0.0001). As revealed by the multivariate analysis results, the marital status was an independent favorable prognostic factor, in which the married groups showed better CSS [hazard ratio (HR): 0.870; 95% confidence interval (CI): 0.808–0.938; p < 0.001] as well as OS (HR: 0.871; 95% CI: 0.810–0.936; p < 0.001). According to the results of subgroup analysis, the CSS and OS survival of married groups were better than the unmarried groups in almost all the subgroups. Conclusion Marital status is an independent favorable prognostic indicator of MPM. Poor prognosis in unmarried patients is likely to be related to insufficient treatments and socioeconomic and psychosocial factors.